Limiting rights : the dilemma of judicial review - Hiebert, Janet, 1960- (McGill-Queen's University Press, 1996)
"In Limiting Rights Janet Hiebert addresses a dilemma of judicial review that threatens to undermine claims that what courts do can be distinguished from the discretionary decisions of policy makers and raises concerns about whether judicial review of the Charter of Rights and Freedoms is consistent with democratic principles. Limiting Rights is an in-depth exploration of who is, and who should be, responsible for determining whether legislation that conflicts with the entrenched rights of the Charter should nevertheless be upheld as a reasonable limit on protected rights."--Jacket